Geopolitical factors affecting childhood nutrition: Iraqi case - Huda Sabah Al-Jadiri; Besmah M. Ali; Jawad K. Al-Diwan (مجلة كلية الطب, 2021)
In Iraq, child’s health had been deteriorated over three turbulent decades starting from the huge and rapid degradation of the country infrastructure by Iraq –Iran war (1980-1988), Gulf War in 1991, and economic sanction.